When public spending goes local: Agricultural expenditure at a key stage in Ghana’s decentralisation reform - Mogues, Tewodaj; Owusu-Baah, Kwaku (UTS ePress, 2020)
This paper provides a qualitative analysis that highlights the implications on agricultural services of a key stage in decentralisation reforms in Ghana. We assess the status of agricultural expenditure decentralisation and draw out the likely implications for agricultural service delivery and national strategies. The study finds that agricultural officers at all levels (national, regional and district) had concerns about the implementation of the new decentralisation reform. These included budget cuts and delays in releases that coincided with the reform period; the transfer of staff from the civil service to the local government service; and a sense that agriculture may receive less attention when allocation of government resources becomes the preserve of assemblies and district chief executives, rather than the central agricultural ministry. The structural changes also meant that agricultural local government staff now needed to learn to ‘market’ the value of their public services to local government leadership, in order to protect resources for agriculture. The decentralisation reform also necessitated new public expenditure reporting practices to ensure a clear overview of sectoral spending across government tiers.